Emirati women’s problems between political and societal empowerment: A case study of the Emirates - Abu Al-Khair, Omaima (Al-Adab Journal, 2019)
This study is based on the premise that the political empowerment of women in the UAE by the state and its institutions moved faster than their social or community empowerment. This is due to the fact that social and cultural heritage still exercises its influence on Emirati women despite the decline in the influence and domination of the past. This heritage still affects the status of women in the country, thereby blocking their path towards social advancement. This study subsumes under the qualitative approach. It is based on deliberate a sample of 23 Emirati women. In-depth interview as a tool for data creation/generation is used in this study. The study is informed by the feminist theory and social gender in data analysis. The results of the study points to the continuity of the dominance of the masculine authority over women in the emirati society. This is exercised by the father, stepfather, husband, and brothers. This domination is exercised specifically over women’s lives in the areas of education, work, and marriage.